New Sheet Editions of Chamber Works by Ukrainian Composers - Syuta, B. (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Kyiv Avant-garde: Chamber music anthology. Kyiv: Muzychna Ukraina, 2020. Chamber music anthology: Stankovych. Ishchenko. Bibik. Kyiv: Muzychna Ukraina, 2021